Insights on the Hair Keratin Structure Under Different Drying Conditions - José Pedro Carvalho; Carla Silva; Madalena Martins; Artur Cavaco-Paulo (Journal of Natural Fibers, 2023)
It is important to understand the patterns of hair keratin integrity caused by drying methods. No previous information exists in the literature to compare different drying conditions needed to assess physical changes in the hair keratin. We used human hair for these experiments. We found that different drying conditions greatly influence the wearing fatigue of the hair fibers. Using a microfiber towel (80% polyester/20% nylon) to remove the excess water seems to better retain the integrity of human hair when compared to drying with a blow-drier or a cotton towel. Hair dried with a microfiber towel showed strong intensity bands at 1664 cm-1 consistent with an alpha-helix structure, while these bands were absent in the spectrum of the hair dried with a blow-drier or a cotton towel. Fatigue recovery of the hair sample dried with a microfiber towel showed much higher wear resistance when compared with the cotton towel and blow-drier processes. These findings were supported by FTIR (Fourier transform infrared) which aided in the elucidation of the secondary structure of alpha-keratin and its effect in the stabilization of hair fibers. When hair samples were exposed to high temperatures, DSC (Differential Scanning Calorimetry) profiles provided information about the movement of water molecules from the fiber, being the enthalpy for hair dried with microfiber towel the highest value. Contributions from damage, friction, and heat were correlated with the molecular structure, in particular, the alpha-helixes predicting that drying condition using a microfiber towel is the process that better preserves hair integrity.